The Biblical Roots of Meditation and an Example of their Development in the History of the Catholic Church in China (The Macau Ricci Institute Journal, 2020)
This paper consists of two parts. First, it aims to show how the Bible regards meditation and similar prayer practices. The analysis will start with collecting and explaining the primary Hebrew and Greek terms related to meditation (e.g. הגה haga(h), ‘to murmur’, ‘to meditate’; שיׂח siyah, ‘to speak’, ‘to meditate’) and their use in the Bible. Some Biblical examples of the meditative prayer will also be shown. These analyses and examples will provide a number of features which constituted meditation or were characteristic to it in the Old Testament times and early Christianity. Such features include (but are not limited to) the following characteristics: 1) Meditation was always directed to God; it was a prayerful relationship with God. 2) Meditation often started with, and even consisted of, the reciting of a Biblical text (or some other pious texts) from memory or reading it in an undertone. 3) Meditation was connected with the constant repeating of the same Biblical (or pious) phrase and committing it to memory. In times when possessing a written scroll was a luxury, people depended on their memory much more than nowadays, and frequent repeating was necessary to learn the words of the Bible by heart or not to forget them. Second, the paper presents one of the prevalent prayers in the history of the Catholic Church in China, the Rosary, which contains clear traces of the Biblical teaching about meditation. The paper will conclude with a concise summary of the connection between the Biblical roots of meditative practices and this prayer which forms a part of the spiritual heritage of the Chinese Catholics throughout their history.